MANAJEMEN PENGEMBANGAN KELEMBAGAAN DI MIN 2 PRINGSEWU DAN MI MIFTAHUL IMAN - Hamidah, Putri Wasilatul; Subandi, Subandi; Dermawan, Oki (Raudhah - Proud To Be Professional, 2025)
This study aims to analyze the management of Islamic education development at MIN 2 Pringsewu and MI Miftahul Iman, two rural-based Islamic schools that have successfully demonstrated significant educational quality despite limited resources. The research adopts a qualitative case study approach, with data collection through in-depth interviews, observations, and documentation. The findings show that both educational institutions apply the POAC (Planning, Organizing, Actuating, Controlling) management principles, focusing on careful planning, efficient resource organization, inclusive implementation involving all community members, and strict monitoring of existing programs. Furthermore, the development of human resources, strengthening religious values, and the implementation of flagship programs such as the Tahfidz al-Qur'an program are key priorities in enhancing educational quality. Despite facing challenges such as limited facilities, infrastructure, and funding, the active involvement of school leadership, teachers, and the community plays a crucial role in creating innovations and adapting educational programs. This study concludes that adaptive management based on Islamic values, which is responsive to local conditions, can improve the quality of Islamic education in rural areas. The implications of this finding suggest the need for the development of a more integrated and community-based model of Islamic education management to maximize the potential available in rural settings.